Possibility of prognostication for unfavorable results of the pancreaticoduodenal resection on background of the obturation jaundice syndrome - P. T. Muraviov; B. S. Zaporozhchenko; I. E. Borodaev; V. G. Shevchenko (Клінічна хірургія, 2019)
Objective. To determine the possibility of prognostication of unfavorable course of postoperative period in the aspect of the planned pancreaticoduodenal resection for focal affection of pancreaticoduodenal zone on background of obturation jaundice.